1974
DOI: 10.1029/jc079i015p02177
|View full text |Cite
|
Sign up to set email alerts
|

Short-period fluctuations in the fair-weather electric field

Abstract: An electrometer was developed to measure the voltage on a copper screen used as a passive antenna 1 m above the ground. An array of three antennas, arranged first downwind and then crosswind, provided data concerning the time variation of the atmospheric potential gradient in the range of frequencies between 0.004 and 0.06 Hz. Results indicated that the fluctuations in the field are primarily associated with drifting clouds of space charge 135-425 m in diameter that are near the level of the antenna. The drift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The results for the spectral indexes of these pulsations, available in the literature, are based on episodic measurements and are quite fragmentary (see [ Anisimov et al , 2001] for a comprehensive review). Using twelve 1‐hour time series data, Yerg and Johnson [1974] pointed out that the fluctuation spectrum of the vertical component of the electric field falls as f −2.2 (in different experiments the spectral index varied from −2.4 to −2.0) at the frequencies of 0.004–0.06 Hz. Anderson [1982] presented the fluctuation spectra of the electric‐charge density, whose indexes varied from −7/3 to −5/3 in the case of ground‐based measurements and from −9/3 to −8/3 if measurements were performed above sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…The results for the spectral indexes of these pulsations, available in the literature, are based on episodic measurements and are quite fragmentary (see [ Anisimov et al , 2001] for a comprehensive review). Using twelve 1‐hour time series data, Yerg and Johnson [1974] pointed out that the fluctuation spectrum of the vertical component of the electric field falls as f −2.2 (in different experiments the spectral index varied from −2.4 to −2.0) at the frequencies of 0.004–0.06 Hz. Anderson [1982] presented the fluctuation spectra of the electric‐charge density, whose indexes varied from −7/3 to −5/3 in the case of ground‐based measurements and from −9/3 to −8/3 if measurements were performed above sea surface.…”
Section: Introductionmentioning
confidence: 99%
“…In a system moving with the mean flow velocity, changes of the structures of charge are relatively small even within the band of frequencies lower than considered in the present paper [Yerg and Johnson, 1974]. This is the reason for which, besides homogeneity and local isotropy, frozen turbulence approximation is assumed in this paper.…”
Section: Introductionmentioning
confidence: 74%
“…These fluctuations may confuse and mislead a researcher upon a search of simultaneous geomagnetic and atmospheric electricity pulsations. Periodic fluctuations of the atmospheric potential gradient and vertical atmospheric current J z in the range of Pc4-5 frequencies were observed by Yerg and Johnson, (1974) and in the Pc1 and Pc3 bands by Anisimov et al (1984). These fluctuations were not coherent with geomagnetic pulsations, so authors suggested that they may be caused by nonmagnetospheric sources, e.g., infrasound emissions from distant meteorological sources.…”
Section: Discussionmentioning
confidence: 99%